The relationship between social networking sites usage and psychological distress among undergraduate students during COVID-19 lockdown - Al-Dwaikat, Tariq N. (Heliyon, 2020)
During the outbreak of the COVID-19 pandemic, interpersonal interactions are restricted to social networks. Undergraduate students are isolated in their homes and dorms. Loneliness is closely related to psychological distress. Fear of contracting the disease will worsen psychological distress. The purpose of this study was to assess the severity of depression, anxiety, and stress symptoms among undergraduate students and their relationships with social networking sites usage during the COVID-19 lockdown. An online survey was used to recruit 456 participants for this cross-sectional descriptive study. Self-reported questionnaires were used to collect data on students' demographics, depression, anxiety, stress, and social networking usage. The results revealed that the majority of students had symptoms of depression (74.1%), anxiety (59.6%), and stress (61.2%). Female students had higher depression and anxiety symptoms than males. Senior-level students' psychological distress symptoms were significantly different from those of junior level. The largest percentage of students (91.9%) used social networking sites for entertainment. The academic usage of social networking sites was negatively (p < .05) correlated with depression and stress scores, while entertainment usage was positively correlated with anxiety. Age was not found to be significantly correlated with psychological distress. Academic and entertainment use of social networking sites were successfully associated with psychological distress symptoms after controlling for demographics. During this unprecedented time of undergraduate students’ course of study, they were experiencing higher than average distress symptoms. These symptoms could be mitigated by continuing the regular academic activities and delivering the most accurate up-to-date information on the COVID-19 through social networking sites.